The Effects of Nursing Care Based on Watson’s Theory on Self-Care Ability in Patients with Congestive Heart Failure - Sima Babaei; Masoud Etedali; Masoumeh-Sadat Mousavi (Iranian Journal of Nursing and Midwifery Research)
Background: Patients with Congestive Heart Failure (CHF) require continuous self-care to manage potential complications and adverse effects of the disease. This study aims to evaluate the impact of Watson’s care model on the self-care ability of these patients. Materials and Methods: This clinical trial was conducted between November 2021 and July 2022 on 72 patients with CHF at a cardiovascular research hospital in Esfahan, Iran. Participants were randomly assigned to either the intervention or control group. The intervention group received care based on Watson’s theory, which included audio recordings to reduce anxiety and enhance hope, individualized sessions to improve knowledge about the disease and its complications, and a 3-month telephone follow-up. Both groups completed a self-care ability questionnaire before, immediately after, and 3 months after intervention. Data were analyzed using statistical tests, including analysis of variance, Kolmogorov–Smirnov, analysis of covariance, and paired t-test. Results: The findings demonstrated a significant difference in the total self-care ability scores within the intervention group before, immediately after, and 3 months following the intervention (F1,67 = 15.73, p < 0.001). Three months after the intervention, the mean self-care ability score was 77.65 in the control group and 123.82 in the intervention group. Conclusions: The study suggests that a care program based on Watson’s theory is an effective and cost-efficient approach to enhancing self-care ability in patients with CHF.